TINJAUAN YURIDIS UNDANG-UNDANG NOMOR 20 TAHUN 2001 PERUBAHAN ATAS UNDANG-UNDANG NOMOR 31 TAHUN 1999 TENTANG PEMBERANTASAN TINDAK PIDANA KORUPSI TEKAIT DENGAN PENJATUHAN SANKSI PIDANA TERHADAP KORUPSI MENURUT PASAL 2 DAN KORUPSI MENURUT PASAL 3 - DESTI SYAF PUTRI; Emilda Firdaus; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Corruption is a form of misappropriation of state money or a company for the personal benefit of a group or a type of corruption can be seen in the corruption eradication law that is law number 20 of 2001 amendments to law number 31 of 1999 as for examples of types of corruption eradication, namely corruption contained in article two and article three. The difference between corruption contained in article two and article three is the legal jek soup where in article two the law is ready for everyone while in article three the legal subject is everyone who has a position or position or means avaible to him or can categorized as state officials, another difference is that the minimum criminal formula, especially in article two, yhe specific minimum criminal is higher than in article threeThis type of research can be classified in the type of normative legal research or literature study because this research conducts research on the level og legal synchronization.From the results of research conducted it can be concluded that the imposition of special minimum criminal sanctions in article two and article three is not in accordance with the value of justice and legal certainty because the specific minimum criminal in article two whereas the biggest opportunity for corruption carried out by legal subjects contained in article three and it should be necessary to renew the law on the eradication of corruption, especially in the formulation of special minimum criminal in article two and article three of the law on eradicating corruption.Keywords : Eradication – Criminal Act – Corruption – Criminal Sanctions